Chocolate milk and endurance exercise recovery: protein balance, glycogen, and performance - Lunn, W. R.; Pasiakos, S. M.; Colletto, M. R.; Karfonta, K. E.; Carbone, J. W.; Anderson, J. M.; Rodriguez, N. R. (Medicine & Science in Sports & Exercise, 2012)
Abstract Purpose: This study examined effects of fat-free chocolate milk (MILK) consumption on kinetic and cellular markers of protein turnover, muscle glycogen, and performance during recovery from endurance exercise.